PEMBANGUNAN PASAR SEHAT KRAMATMULYA DESA KELAPA GUNUNG KABUPATEN KUNINGAN SEBAGAI OPTIMALISASI POTENSI UMKM - Darto, Darto; Aditiany, Savitri; Fauzi, Muhammad Rifqi (Universitas Komputer Indonesia, 2025)
Due to its rich natural resources, Kramatmulya District is home to a wide variety of food and local specialty products. This abundance has led to approximately 2,003 micro, small, and medium enterprises (MSMEs) conducting trade to support their livelihoods and supply the community's food needs. Despite this, these MSMEs have encountered difficulties, such as a shortage of skilled labor, antiquated production infrastructure, outdated marketing approaches, and a 30% decline in revenue during the COVID-19 pandemic. This